Facilitating a collegial department in higher education strategies for success - Cipriano, Robert E. 1945- (Jossey-Bass resources for department chairs, 2011)
"Collegiality is a key element that department chairs value when recommending faculty members for tenure. This practical book (written for chairs and deans) offers a reference of "what to do" proactively so that departments function effectively. The book is filled with the most current ideas and research of what has worked to enhance the climate, culture, and collegiality in the department, as well as the university. The book also includes case law relative to collegiality or lack of collegiality in higher education so that readers will get a helpful guide to nurturing a more collegial department--in a way, preventing toxic situations from arising or worsening"